Assembly of Clay Nanotubes on Cotton Fibers Mediated by Biopolymer for Robust and High‐Performance Hemostatic Dressing. Issue 1 (10th November 2022) - Feng, Yue; He, Yunqing; Lin, Xiaoying; Xie, Mingyang; Liu, Mingxian; Lvov, Yuri
Abstract: Uncontrollable bleeding from military conflicts, accidents, and surgical procedures is a major life‐threatening factor. Rapid, safe, and convenient hemostasis is critical to the survival of bleeding patients in prehospital care. However, the peel‐off of hemostats such as kaolinite sheets from the cotton fibers often poses a risk of distal thrombosis. Here, an efficient clay hemostat of halloysite nanotubes is tightly bound onto commercial cotton fibers, which is capillary mediated by biopolymer alginate with Ca 2+ crosslinking. The robust clay nanotube dressing materials maintain high procoagulant activity after harsh water treatment, and only a few residuals of halloysite exist in the wound area. Compared with commercial hemostat QuikClot Combat gauze, halloysite‐alginate‐cotton composite dressing exhibits hemostatic properties both in vivo and in vitro with high safety. The hemostatic mechanism of the dressing is attributed to activating platelets, locally concentrating clotting components in the nanoclay, halloysite coagulation factors, and alginate cross‐linked with Ca 2+ . This work inspires robust self‐assembly of clay nanotubes on textile fibers and offers a hemostatic material with balanced high hemostatic activity, minimal ingredient loss, and biocompatibility. The robust dressing based on halloysite tightly bounded cotton shows great potential for military, medical, and civil bleeding control with low health risks. Abstract : A clay hemostat of halloysite is tightly bound onto cotton fibers and capillary mediated by biopolymer alginate with Ca 2+ crosslinking. This dressing maintains high clotting activity after water treatment, and only few residuals of halloysite exist in the wound. Halloysite‐alginate‐Ca 2+ network promotes clotting through multiple interface–blood interactions. The organic–inorganic composite dressing balances robustness, effectiveness, and biosafety.